A new desiccation-resistant midge from ephemeral rock pools in South Africa, Polypedilum (Pentapedilum) cranstoni sp. nov. (Diptera: Chironomidae) - Cornette, Richard; Motitsoe, Samuel N.; Mlambo, Musa C. (Zootaxa, 2022)
One newly described species of Chironomidae, Polypedilum (Pentapedilum) cranstoni sp. nov., was discovered in ephemeral rock pools from the Maloti-Drakensberg mountains in South Africa. Desiccation-resistant larvae were obtained from bottom sediments of rock pools that had been dry for the previous several months. After rehydration, ex situ adults emerged and were collected. The morphology and diagnostic characters of the new species (male and female adults) are described here together with an analysis based on their COI gene sequence.